Biodiversity of Plankton and Microcystin Concentrations in Water Sources at King Mongkut's Institute of Technology Ladkrabang: A Summer Season Toxicity Assessment - Oratai Pengtowong; Suneerat Ruangsomboon (King Mongkut's Agricultural Journal, 2026)
This study investigated the diversity of plankton and the presence of microcystin toxins in water sources around King Mongkut’s Institute of Technology Ladkrabang (KMITL) during the summer season, aiming to assess biodiversity and potential risks to water users. Samples were collected monthly from 10 stations. A total of 92 species of phytoplankton, belonging to 64 genera, 6 classes, and 3 divisions, were identified. The division Chlorophyta exhibited the highest species diversity (31 genera, 74 species), while the class Cyanophyceae showed the highest abundance (0.14-374.78 × 104 units/L), with Chroococcus spp. being the most dominant genus (372.58 × 104 units/L). Zooplankton comprised 22 genera and 11 species from 3 phyla, with Protozoa showing both the highest diversity (12 genera) and abundance (3,714.53 units/L), and Difflugia being the most abundant genus (1,750.11 units/L). Six genera of potentially toxin-producing cyanobacteria were detected: Oscillatoria, Microcystis, Lyngbya, Pseudanabaena, Anabaena, and Anabaenopsis, with a combined abundance ranging from 0-7.61 × 104 units/L. However, microcystin toxins were not detected in any water samples, suggesting that toxic plankton levels were insufficient to produce or accumulate detectable toxins. Biodiversity indices, including the Shannon-Wiener index (0.17–1.78), evenness (0.046–0.508), and species richness (2.11–4.66), indicated low to very low biodiversity in the studied waters. Positive correlations were observed between Cyanophyceae abundance and both salinity and conductivity, while Euglenophyceae, Chrysophyceae, and Dinophyceae correlated positively with light intensity. Protozoa abundance was positively associated with total dissolved solids.
Keywords: Aquatic Ecosystems and Phytoplankton Dynamics; Marine and coastal ecosystems; Microbial Community Ecology and Physiology